Unexpected diversity of Microscydmus Saulcy & Croissandeau in Japan (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
The genus Microscydmus Saulcy & Croissandeau is recorded for the first time from the Japanese Archipelago. Eight species are described: Microscydmus okinawanus sp. n., M. oharaensis sp. n., M. nishimeanus sp. n., M. kochiensis sp. n., M. elytratus sp. n., M. tibialis sp. n., M. yusuharanus sp. n., and M. omogonus sp. n. All new species are placed in the nominotypical subgenus, and Japan becomes a country that houses the greatest recorded species richness of Microscydmus (s. str.). The new species are distributed on Shikoku and in the Ryukyus. A novel character was found, previously unknown in Microscydmus: a pair of long lateral setae on the posterior margin of vertex, clearly visible in some of the newly described species. These setae are not thicker than surrounding ones, but stand out because of their remarkable length. A re-examination of SEM images obtained during previous studies confirmed the presence of these setae also in M. nanus, the European type species of the genus, in which, however, these setae are obscured by surrounding vestiture. Among Glandulariini, such a pair of setae has been known only in the extinct Upper Cretaceous Scydmobisetia Jałoszyński & Yamamoto.